Cladistic analysis of Caseidae (Caseasauria, Synapsida): using the gap‐weighting method to include taxa based on incomplete specimens. (23rd September 2015) - Romano, Marco; Nicosia, Umberto; Angielczyk, Kenneth
Abstract Occupying the role of primary consumer and having an early–middle Permian age range, caseids (Caseasauria, Synapsida) are fundamental to the interpretation of the early history of terrestrial vertebrate ecosystems. Despite this importance, no comprehensive, species‐level phylogenetic study of Caseidae has yet been performed. Herein, we present a phylogenetic analysis of the group, using gap weighting to include poorly known taxa. Besides the description and comments on the resultant topologies, some more general issues concerning cladistic methodologies are briefly addressed. This study highlights the importance of a total‐evidence approach, including as many within‐group taxa and characters as possible. Continuously varying characters, in the form of indices derived from measurement of individual skeletal elements, proved to be highly important, adding significantly to the resolution of, and support for, recovered trees. The utility of the postcranial skeleton in understanding relationships among basal synapsids is highlighted.